Assessment of landscape composition and configuration via spatial metrics combination: conceptual framework proposal and method improvement. - Machado, Rui (2018)
Landscape transformations have been a central topic in landscape ecology due to their influence on ecosystem services and biodiversity conservation. Landscape dynamics can be very complex and one of the most difficult issues to analyse is the contribution and the effects of landscape composition and configuration changes to the overall impact. We enhanced an existing approach designed to assess landscape transformation via metrics combination. Based on the area and the number of patches, we defined a Landscape Dynamics Typology (LDT) with eight different dynamics. The agro-forestry areas dynamics between 1990 and 2006, in Portugal, is presented as a practical example to show the implementation steps and the outputs obtained. A diagnostic tree is provided to help identify which dynamics are present. This new method provides detailed results concerning the location of the different dynamics within a landscape. The LDT is a versatile tool and is able to accommodate upgrades.